KEWARISAN DALAM PERSPEKTIF AL-QURAN (Mengungkap Filosofi porsi Bagian laki-laki Dan perempuan 2:1) - Arsal, Arsal (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
Regulation of inheritance in the Quran, especially porti parts that are not the same between men and women make the debate among scholars that ultimately lead to the opinion that the inheritance in the Quran nuanced muthlak justice as it is applied, and the other opinion says impression that there was discrimination provisions that can be adapted to the changed dynamics of the community. This phenomenon needs to be responded by reviewing and understanding how the philosophical portion of the parts in the verses of the Koran.